COMPARACIÓN DE LA RADIOGRAFÍA SIMPLE Y LA TOMOGRAFÍA COMPUTARIZADA EN EL DIAGNÓSTICO DE HERNIA DISCAL TIPO 1 EN PERROS - Donaires V., Rosmery (2013)
The objectives of the study were to describe the radiologic findings of plain radiography in animals with suspected herniated disc and to establish coincidences with the computed tomography (CT) examination. Sixteen dogs were studied, whose neurological evaluation revealed a neurological dysfunction compatible with thoracolumbar spinal cord compression and a magnitude of injury of grade III or higher. Two patients failed to show signs of disc herniation in both tests and were withdrawn from the study. Plain radiographies identified 14 animals with radiographic abnormalities consistent with a herniated disc. In 71.4% (10/14) of these cases, the results between radiographic and CT examinations coincided in the diagnosis of the presence of the disease and location of the affected intervertebral space. The radiographic findings most common in animals suspected to herniated disc type 1 were narrowed intervertebral space (13/14), decreased size intervertebral foramen (8/14) and opacity of the intervertebral foramen (4/14). The most common CT findings in animals with herniated disc type 1 were the presence of disc material in the spinal canal (12/12), spinal canal stenosis (12/12), and the foraminal space stenosis (8/12). The intervertebral space most affected thoracolumbar segment was the L1-L2 (4/12). The results show that plain radiography cannot be regarded as an absolute indicator in the diagnosis of type 1 disc herniation, and it should be complemented with a CT examination.